2016
DOI: 10.1007/s00705-016-2920-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and biological characterization of a new potyvirus in lettuce

Abstract: A potyvirus causing necrosis and leaf distortion on lettuce was found in the Lazio region of Italy. Host range analysis showed its ability to infect only Chenopodium quinoa and C. amaranticolor in addition to some lettuce cultivars. The virus could be transmitted by aphids of the species Myzus persicae. The complete 9829-nt genome was characterized. BLAST analysis of sequence of the complete encoded polyprotein showed that the most closely related virus is asparagus virus 1, with 52 % amino acid sequence ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Isolate 7091 shared 98% nt identity (99% aa identity) with a potyvirus recently described as lettuce Italian necrotic virus (LINV; accession ; Ciuffo et al ., ). For isolate 7098, the closest virus identified from whole genome sequence analysis was vanilla distortion mosaic virus (VDMV; 55% nt identity, 62% aa identity).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Isolate 7091 shared 98% nt identity (99% aa identity) with a potyvirus recently described as lettuce Italian necrotic virus (LINV; accession ; Ciuffo et al ., ). For isolate 7098, the closest virus identified from whole genome sequence analysis was vanilla distortion mosaic virus (VDMV; 55% nt identity, 62% aa identity).…”
Section: Resultsmentioning
confidence: 97%
“…The molecular studies showed that isolates 7091 and 7098, collected on lettuce plants with symptoms in southeastern France in 2012, belonged to two different potyvirus species. Isolate 7091 shared 98% nt sequence identity over the whole genome with a potyvirus isolate collected in Italy in July 2014 in L. sativa ‘Romana’ (Ciuffo et al ., ) and described as a member of the tentative new species LINV. The Italian isolate induces necrosis and leaf distortion on lettuce, similar to the symptoms observed for isolate 7091.…”
Section: Discussionmentioning
confidence: 99%
“…Lettuce ( Lactuca sativa , family Asteraceae) crops are affected by several potyviruses (genus Potyvirus ; family Potyviridae ), including Lettuce mosaic virus (LMV), Turnip mosaic virus (TuMV), Bidens mottle virus (BiMoV), Endive necrotic mosaic virus (ENMV) and lettuce Italian necrotic virus (LINV) (Christie et al ., ; Zink et al ., ; Zitter & Guzman, ; Provvidenti & Hampton, ; Blancard et al ., ; Ciuffo et al ., ; Desbiez et al ., ). LINV was recently described in lettuce crops in Italy and southeast France and induces severe necrosis and plant wilting, leaf distortion and/or vein clearing.…”
Section: Introductionmentioning
confidence: 98%
“…However, experimental inoculations showed that it can infect plants of other species in the family Asteraceae ( Calendula spp., Cichorium spp., Helianthus annuus , Tragopogon pratensis and Zinnia elegans ) and Nicotiana benthamiana (Desbiez et al ., ). Transmission by Myzus persicae (Homoptera: Aphididae) was demonstrated experimentally (Ciuffo et al ., ; Desbiez et al ., ). LINV is phylogenetically related to LMV in the genus Potyvirus .…”
Section: Introductionmentioning
confidence: 98%
“…In recent years, several novel viruses have been characterized in lettuce crops (Ciuffo et al 2016;Svanella-Dumas et al 2018, Verbeek et al 2014, while the main viruses infecting lettuce in Europe or in Central America have been respectively reviewed in Moreno et al (2012) and Pavan et al (2008). Lettuce mosaic virus (LMV, Potyvirus) is probably the most important virus of lettuce worldwide (Pavan et al 2008).…”
Section: Introductionmentioning
confidence: 99%